Anxiety is associated with appetitive traits in university students during the COVID-19 pandemic - Kathryn E. Coakley; Huyen Le; Spirit Rae Silva; Aspen Wilks (Nutrition Journal, 2021)
Abstract Background COVID-19 has impacted mental health globally, however, associations between anxiety and appetitive traits during the pandemic are unreported. This study evaluated anxiety symptom severity and associations with appetitive traits in students at a large public University in the U.S. during the pandemic. Methods Current undergraduate and graduate/professional students completed a cross-sectional survey in fall 2020. Demographic information, anxiety symptoms in the past 2 weeks assessed by the Generalized Anxiety Disorder Scale (GAD-7), and appetitive traits assessed by the Adult Eating Behavior Questionnaire (AEBQ) were evaluated. Mean scores for eight AEBQ scales (four food approach and four food avoidance traits) were calculated. Differences in mean scores were examined between participants with moderate to severe anxiety symptoms (GAD-7 score ≥ 10) and those with mild to no anxiety symptoms (GAD-7 score < 10) via independent samples t-tests and effect sizes. Associations between GAD-7 score and individual appetitive traits were also examined, adjusting for age and gender. Results Of the 1243 students who completed the survey (57% undergraduates; mean age = 26.5 years), 51.9% reported moderate to severe anxiety symptoms. Groups experiencing the highest degree of moderate to severe anxiety symptoms included transgender, gender fluid, and other-gendered participants (73.6%); the youngest age group [18–20 years (62%)]; undergraduate students (60.7%); and Hispanic/Latinx participants (57.7%). Participants with moderate to severe anxiety symptoms had higher scores for most food approach and avoidance traits but lower scores for enjoyment of food than those with mild to no anxiety symptoms. Effect sizes were largest for hunger and emotional over-eating (Cohen’s d = 0.31 and 0.30, respectively). Adjusting for age and gender, GAD-7 score was significantly and positively associated with hunger, emotional over-eating, food and satiety responsiveness, and food fussiness and negatively associated with enjoyment of food. Conclusions Over half of students at a U.S. University reported moderate to severe anxiety symptoms during COVID-19. More severe anxiety symptoms were associated with increased hunger, emotional over-eating, and food and satiety responsiveness and decreased enjoyment of food. Universities must consider strategies to address anxiety, particularly in younger students; transgender, gender fluid, and students of other genders; and across race/ethnicities keeping in mind associations with appetitive traits.